2018
DOI: 10.22467/jwmr.2018.00367
|View full text |Cite
|
Sign up to set email alerts
|

Bullosis Diabeticorum: A Diabetic Bullosis, Commonly Unknown

Abstract: Bullosis diabeticorum (BD) is a distinct, spontaneous, noninflammatory, and blistering lesion that develops predominantly in the acral skin of patients with diabetes mellitus (DM). BD is a rare disease that develops in patients with longterm DM and not well known to physicians and often fails to be diagnosed. The lesions are known to spontaneously heal in most patients in 2 to 6 weeks. Wound care is required to prevent secondary infection of the blisters. However, if infection develops and progresses to necros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Although discovered more than 80 years ago by Professor Kramer in 1930, it took about 37 years for this condition to be described in the medical literature by Cantwell and Martz under the name by which it is known today: bullosis diabeticorum [ 4 - 6 , 10 , 11 ]. It is a very rare skin condition, with only a hundred case descriptions in the medical literature and is characterized by sudden onset bullous lesions with no history of trauma, most of whom have poorly controlled type 2 diabetes [ 2 , 11 , 12 ]. Our patient was admitted for not being followed up by a healthcare professional for her diabetes, and unfortunately HBA1C was not available at the center, and the patient could not afford to have it done elsewhere.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although discovered more than 80 years ago by Professor Kramer in 1930, it took about 37 years for this condition to be described in the medical literature by Cantwell and Martz under the name by which it is known today: bullosis diabeticorum [ 4 - 6 , 10 , 11 ]. It is a very rare skin condition, with only a hundred case descriptions in the medical literature and is characterized by sudden onset bullous lesions with no history of trauma, most of whom have poorly controlled type 2 diabetes [ 2 , 11 , 12 ]. Our patient was admitted for not being followed up by a healthcare professional for her diabetes, and unfortunately HBA1C was not available at the center, and the patient could not afford to have it done elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…She self-medicated with metformin at irregular doses when she experienced discomfort, knowing that she was diabetic and obese. Kang et al reported observations of Wilson disease over 11 years, leading to the conclusion that there is a correlation between bullosis diabeticorum and uncontrolled hyperglycemia in diabetic patients [ 2 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations